Porous N-doped carbon sheets wrapped MnO in 3D carbon networks as high-performance anode for Li-ion batteries. (10th May 2020) - Huang, Shouji; Li, Huapeng; Xu, Guobao; Liu, Xiong; Zhang, Qi; Yang, Liwen; Cao, Juexian; Wei, Xiaolin
Abstract: We develop a facile and low-cost method to construct porous N-doped carbon sheets wrapped MnO cubes with average size of 150 nm in 3D carbon networks by one-step pyrolysis strategy. The unique and novel nanostructure not only provides holes to promote fast ion transport and conductive framework to enhance the charge transfer, but also effectively supplies an elastic buffer space to accommodate volume expansion during cycling. Furthermore, kinetic analysis and other tests reveal that capacitive-controlled Li storage is a vital way and further oxidation of Mn 2+ to a higher state with cycling contributes a lot of capacity. As a result, the composite electrode shows high specific capacity of 917 mAh g −1 at 0.2 A g −1 after 190 cycles, outstanding rate capability of 328 mAh g −1 at 5 A g −1, and long cycling stability (655 mAh g −1 at 1 A g −1 after 550 cycles, capacity retention of 105%). Furthermore, the composite electrode and LiFePO4 are used as anode and cathode to assemble full cell which also exhibits excellent rate capability and cycling stability, indicating great application potential. The simple and low-cost strategy of synthetizing the unique nanocomposite structure can also be applied to other composite anode materials for lithium-ion batteries.